Nano bismuth particle loaded graphite felt electrode and preparation method thereof
The formation of nanoscale bismuth particles on the graphite felt electrodes through plasma reduction technology, which solves the problem of slow kinetics of chromium ion redox reactions and frequent side reactions of hydrogen evolution in iron-chromium flow batteries, and significantly improves the efficiency and life of the battery.
Patent Information
- Application Number
- CN202411780189.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The development of iron-chromium flow batteries is restricted by the slow kinetics of the negative electrode chromium ion redox reaction and frequent side reactions of hydrogen evolution, resulting in low battery efficiency and shortened cycle life.
Through plasma reduction technology, bismuth ions adsorbed on the surface of graphite felt fibers are directly reduced to nanoscale bismuth metal particles, forming a graphite felt electrode loaded with nanobismuth particles.
The uniform distribution and high specific surface area of nanoscale bismuth particles are achieved, which significantly improves the catalytic performance of the electrode pair Cr3+/Cr3+ electrical pairs, avoids hydrogen evolution side reactions, and improves the Coulomb efficiency and energy efficiency of the battery.
Smart Images

Figure CN119695175A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of liquid flow battery electrode materials, and in particular to a graphite felt electrode loaded with nano-bismuth particles and a preparation method thereof. Background Art
[0002] As a new type of large-scale energy storage technology, flow batteries have unique advantages, such as independent adjustment of energy and power, high safety, and long cycle life. Among them, iron-chromium (Fe-Cr) flow batteries have become a very promising energy storage technology due to their abundant active material resources, low cost, and environmental friendliness. However, the development of Fe-Cr flow batteries has been restricted by some key technical bottlenecks, mainly in the negative electrode chromium ion (Cr3 + / Cr3 + ) The slow kinetics of the redox reaction and the easy occurrence of hydrogen evolution side reactions on traditional carbon-based electrode materials lead to low battery efficiency and shortened cycle life, making it difficult to meet the requirements of large-scale applications.
[0003] In the prior art, electrodes usually use untreated raw graphite felt or heat-treated graphite felt, but due to the low specific surface area and electrocatalytic activity, the electrochemical catalytic effect on the chromium negative electrode of the battery is poor, and a strong hydrogen evolution side reaction is prone to occur during the charging process. Bismuth (Bi) metal has a unique electronic structure and catalytic properties for Cr3 + / Cr3 + The electrode pair has excellent catalytic activity. The low hydrogen evolution overpotential (higher hydrogen evolution overpotential) of bismuth can effectively inhibit the hydrogen evolution side reaction during the electrochemical reaction and improve the coulombic efficiency and energy efficiency of the battery. In addition, bismuth metal can reduce Cr3 + / Cr3 + The redox overpotential of the electrode couple accelerates the reaction kinetics. Therefore, loading bismuth metal particles on the electrode material has become one of the main ways to improve the performance of iron-chromium flow batteries.
[0004] Traditional bismuth modification methods, such as in-situ electrodeposition and high-temperature reduction, are difficult to meet the needs of large-scale preparation and practical application. The main reasons are as follows: (1) Large particle size and uneven distribution. The bismuth particles prepared by these methods are usually large in size (about several microns), and are unevenly distributed on the electrode surface and easily aggregated, resulting in limited active sites and the inability to fully exert the catalytic effect of bismuth. (2) Complex process and high energy consumption. The high-temperature reduction method needs to be carried out under high temperature conditions, which consumes a lot of energy and has a cumbersome process flow. (3) Easy to block the electrode pores. During the in-situ electrodeposition process, bismuth particles are prone to excessive deposition at the electrode entrance, resulting in pore blockage, affecting the flow of the electrolyte and the stability of the battery performance, because the in-situ electrodeposition method cannot be used to load the bismuth catalyst in the battery stack.
[0005] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a graphite felt electrode loaded with nano-bismuth particles and a preparation method thereof, wherein the bismuth ions adsorbed on the surface of the graphite felt fiber are directly reduced to nano-sized bismuth metal particles by plasma reduction technology. This method can avoid the high temperature and complex process flow in the traditional method, realize a simple and efficient preparation process, and is suitable for large-scale electrode modification.
[0007] The above object of the present invention is achieved by the following technical solution: a method for preparing a graphite felt electrode loaded with nano-bismuth particles, wherein the method comprises the following steps:
[0008] Pre-treating the graphite felt electrode to obtain a hydrophilic graphite felt electrode;
[0009] Immersing the hydrophilic graphite felt electrode in a solution containing bismuth ions, taking it out and drying it to obtain a graphite felt loaded with reduced bismuth precursor crystals;
[0010] The graphite felt loaded with reduced bismuth precursor crystals is treated with plasma to obtain a graphite felt electrode loaded with nano-bismuth particles.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] As a preferred technical solution, the method for preparing the graphite felt electrode loaded with nano-bismuth particles is as follows, wherein the pretreatment is a heating pretreatment, wherein the heating temperature is 400-500° C., and the holding time is 4-5 hours.
[0013] As a preferred technical solution, in the method for preparing the graphite felt electrode loaded with nano-bismuth particles, the concentration of bismuth ions in the solution is 0.01 to 0.04 mol / L.
[0014] As a preferred technical solution, the method for preparing the graphite felt electrode loaded with nano-bismuth particles is characterized in that the drying condition is baking at 80-100° C. for 2-3 hours.
[0015] As a preferred technical solution, the method for preparing the graphite felt electrode loaded with nano-bismuth particles, wherein the graphite felt loaded with reduced bismuth precursor crystals is treated with plasma, comprises:
[0016] placing the graphite felt loaded with reduced bismuth precursor crystals in a plasma cleaning device, adjusting the parameters of the plasma cleaning device to reduce bismuth ions, and obtaining a graphite felt electrode material loaded with bismuth metal particles and bismuth oxychloride particles;
[0017] The graphite felt electrode material loaded with bismuth metal particles and bismuth oxychloride particles is cleaned and dried to obtain the graphite felt electrode loaded with nano-bismuth particles.
[0018] As a preferred technical solution, the method for preparing the graphite felt electrode loaded with nano-bismuth particles, wherein the parameters include: air flow rate of 40-60 ml / min, radio frequency power of 100-150 W, vacuum degree of 10-20 Pa, and cleaning time of 10-20 min.
[0019] As a preferred technical solution, the method for preparing the graphite felt electrode loaded with nano-bismuth particles, wherein the particle size of the nano-bismuth particles is 5 to 10 nm.
[0020] As a preferred technical solution, the method for preparing the graphite felt electrode loaded with nano-bismuth particles is as follows: the solution is a hydrochloric acid solution containing bismuth ions, and the concentration of the hydrochloric acid solution is 1-3 mol / L.
[0021] In a second aspect, a graphite felt electrode loaded with nano-bismuth particles is provided, wherein the graphite felt electrode loaded with nano-bismuth particles is prepared by the preparation method described above.
[0022] In a third aspect, an iron-chromium or all-vanadium liquid flow battery is provided, wherein the iron-chromium or all-vanadium liquid flow battery comprises the graphite felt electrode loaded with nano-bismuth particles as described in the second aspect above.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant technical advantages:
[0024] 1) Nano-scale particles and uniform distribution: The bismuth particles prepared by plasma reduction technology are small in size (5-10 nanometers), uniformly distributed, have high specific surface area and surface activity, and significantly improve the electrode's Cr3 + / Cr3 + Catalytic properties of the electrode pair.
[0025] 2) Simple process and low energy consumption: Plasma reduction technology is carried out at room temperature or low temperature, has low requirements for equipment and environment, low energy consumption, fast reaction speed (completed in 10-20 minutes), and improves production efficiency.
[0026] 3) Avoid pore clogging: Compared with traditional electrodeposition methods, plasma reduction method avoids the problems of particle agglomeration and pore clogging, maintains the pore structure and permeability of the electrode, and maintains good electrolyte fluidity and electrode reaction activity.
[0027] 4) Easy to scale up production: The process is simple, with few operating steps and mild conditions. It does not require complex equipment or a high-energy consumption environment. It is easy to integrate into existing production lines, and can achieve automated and continuous production, thus reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : The scanning electron microscope (SEM) image of the graphite felt electrode material loaded with nano-bismuth particles prepared in Example 1 shows the microscopic morphology of the electrode material surface and the distribution characteristics of the nanoparticles.
[0029] Figure 2 : The X-ray diffraction (XRD) pattern of the electrode material prepared in Example 1 shows the phase composition and crystal structure characteristics of the electrode material.
[0030] Figure 3 : Transmission electron microscope (TEM) morphology images of the electrode material prepared in Example 1 and lattice fringes of the corresponding particles, where (a) and (b) are high-resolution TEM images of metallic bismuth nanoparticles and their lattice fringes, and (c) and (d) are the morphology and lattice structure of bismuth oxychloride particles.
[0031] Figure 4 : The cyclic voltammetry (CV) test curves of the electrode material prepared in Example 1 and the graphite felt electrode in the blank control group (GF is the original graphite felt, TGF is the graphite felt after thermal pretreatment) are compared to compare the electrochemical properties of different electrode materials.
[0032] Figure 5 :The electrode material prepared in Example 1 and the graphite felt electrode in the blank control group were subjected to a current density of 200 mA / cm 2 The charge and discharge curves below reflect the polarization characteristics and capacity performance of the battery.
[0033] Figure 6 : The charge and discharge curves of the electrode material prepared in Example 1 at different current densities (100-300 mA / cm2) demonstrate the rate performance and electrochemical stability of the battery.
[0034] Figure 7 : The rate cycle efficiency diagram of the electrode materials prepared in Example 1, Example 2, and Example 3 and the graphite felt electrode in the blank control group compares the energy efficiency and coulombic efficiency of the electrode materials prepared under different process conditions.
[0035] Figure 8: The rate cycle efficiency diagram of the electrode material prepared in Example 1 and the graphite felt electrode in the blank control group further evaluated the electrochemical performance of the electrode material at different current densities.
[0036] Fig. 9 : The efficiency curve of the electrode material prepared in Example 1 and the TGF electrode after 200 cycles at a current density of 200 mA / cm2 reflects the long-cycle stability of the battery.
[0037] Fig.10 : The charge and discharge capacity curves of the electrode material prepared in Example 1 and the TGF electrode after 200 cycles at a current density of 200 mA / cm2 demonstrate the battery capacity retention capability. DETAILED DESCRIPTION
[0038] The present invention provides a graphite felt electrode loaded with nano-bismuth particles and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementation methods. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and do not mean a necessary sequence, unless otherwise specified that a certain sequence must be followed. The serial numbers themselves, such as "first", "second", etc., assigned to the components herein are only used to distinguish the objects described and do not have any order or technical meaning.
[0040] Example 1
[0041] (1) Thermal pretreatment of graphite felt
[0042] The commercial graphite felt material was cut into samples of 3 cm × 3 cm in size and placed in a muffle furnace for heat pretreatment. The specific conditions were: in an air atmosphere, the temperature was raised to 500 ° C, the heating rate was 10 ° C / min, and the holding time was 5 hours. The heat treatment process is aimed at removing organic impurities on the surface of the graphite felt, increasing the surface oxygen-containing functional groups (such as hydroxyl, carboxyl, etc.), and improving the hydrophilicity of the graphite felt and its adsorption capacity for metal ions.
[0043] (2) Preparation and impregnation of bismuth ion solution
[0044] Weigh 0.126g (about 0.4mmol) of high-purity BiCl3, dissolve it in 20mL of 2mol / L hydrochloric acid, stir it thoroughly until it is completely dissolved to form a uniform and transparent bismuth ion solution. Immerse the heat-pretreated graphite felt sample in the solution and let it stand at room temperature (about 25°C) for 8 hours to ensure that the bismuth ions are fully adsorbed on the surface of the graphite felt fiber. This process utilizes the hydrophilicity of the graphite felt surface and the complexation of oxygen-containing functional groups on metal ions.
[0045] (3) Drying
[0046] After the impregnation is completed, the graphite felt sample is taken out, the excess solution on the surface is gently shaken off, and the sample is placed in a vacuum drying oven and dried at 80°C for 2 hours to remove the adsorbed moisture and unreacted free bismuth ions to obtain a graphite felt loaded with a bismuth ion precursor.
[0047] (4) Plasma reduction treatment
[0048] The dried graphite felt sample was placed in a plasma cleaning machine for plasma reduction treatment. The specific parameters were set as follows: air atmosphere, gas flow rate 40 mL / min, RF power 150 W, vacuum 10 Pa, and treatment time 10 minutes. In a plasma environment, high-energy active particles (such as electrons, ions, free radicals, etc.) react with bismuth ions adsorbed on the surface of graphite felt fibers to reduce them to metallic bismuth nanoparticles. At the same time, some bismuth ions may react with oxygen to form bismuth oxychloride (BiOCl) particles.
[0049] (5) Cleaning and final drying
[0050] After the reduction treatment, the graphite felt sample was taken out and gently washed with deionized water three times to remove unreacted residues and by-products. Then, it was placed in a vacuum drying oven and dried at 80°C for 2 hours to obtain the final graphite felt electrode material loaded with nano-bismuth particles.
[0051] Characterization of the prepared graphite felt electrode material loaded with nano-bismuth particles
[0052] (1) SEM analysis Figure 1 )
[0053] The surface morphology of the electrode materials was observed using a scanning electron microscope (SEM). Figure 1 As shown, the graphite felt surface is uniformly loaded with flaky bismuth oxychloride (BiOCl) particles, with a particle size of about 50 to 100 nm. These flaky particles are beneficial to increase the specific surface area and active sites of the electrode.
[0054] (2) XRD analysis Figure 2 )
[0055] X-ray diffraction (XRD) was used to analyze the phase composition of the electrode material. Figure 2 As shown in the figure, the characteristic diffraction peaks of metallic bismuth (Bi) and bismuth oxychloride (BiOCl) appeared, proving that bismuth ions were successfully converted into metallic bismuth and BiOCl during the plasma reduction process. The presence of these two substances helps to improve the electrochemical catalytic activity of the electrode.
[0056] (3) TEM analysis Figure 3 )
[0057] Transmission electron microscopy (TEM) is used to observe electrode materials at a higher resolution. Figure 3 As shown in (a) and (b), metallic bismuth nanoparticles with a particle size of about 5 nm and their clear lattice fringes were observed, further confirming the successful preparation of nanoscale bismuth particles. Figure 3 (c) and (d) show the morphology and lattice structure of BiOCl particles. The presence of these nanoparticles provides more active sites for electrochemical reactions.
[0058] Electrochemical performance test of the prepared graphite felt electrode material loaded with nano-bismuth particles
[0059] (1) Cyclic voltammetry (CV) test Figure 4 )
[0060] The electrochemical performance of the electrode material was evaluated using a traditional three-electrode system. The working electrode was a graphite felt electrode loaded with nano-bismuth particles, and the control group was pristine graphite felt (GF) and graphite felt after thermal pretreatment (TGF). The reference electrode was a saturated calomel electrode, and the auxiliary electrode was a platinum sheet. The electrolyte was a 3 mol / L hydrochloric acid solution, the active substance concentration was 0.1 mol / L CrCl3, and the scan rate was 20 mV / s. Figure 4 As shown in the figure, compared with the control group, the electrode material loaded with nano-bismuth particles exhibited significantly enhanced electrochemical catalytic activity. The redox peak current increased, the peak potential difference (ΔE) decreased, and the redox peak current ratio was close to 1, indicating that the electrode pair Cr3+ / Cr2+ had good reversibility and fast charge transfer ability. Due to the hydrophobic surface, GF could not effectively adsorb chromium ions, and almost no obvious redox peak was observed; although the hydrophilicity of TGF was improved, only a weak oxidation peak appeared due to the lack of catalytic active components.
[0061] (2) Constant current charge and discharge test ( Figure 5 and Figure 6 )
[0062] In the flow battery device, the Neware battery test system was used to perform constant current charge and discharge tests on the battery. The negative electrode was graphite felt loaded with prepared nano-bismuth particles, the positive electrode was graphite felt (TGF) after heat pretreatment, the separator was Nafion 212, and the effective area of the whole battery was 2cm×2cm. The electrolyte was: negative electrode: 1mol / L CrCl3, 3mol / L HCl; positive electrode: 1mol / L FeCl2, 3mol / L HCl. The electrolyte volume was 25mL and the flow rate was 30mL / min. The test voltage range was 0.7V to 1.3V. Figure 5 As shown, at a current density of 200 mA / cm2, the battery loaded with nano-bismuth particle electrodes exhibited lower polarization voltage and higher discharge capacity, and the performance was significantly improved compared with the blank control group. Figure 6 The charge and discharge curves at different current densities (100-300 mA / cm2) are shown. As the current density increases, the discharge capacity of the battery decreases, but still maintains good rate performance.
[0063] Battery performance analysis
[0064] (1) Cycle efficiency ( Figure 7 and Figure 8 )
[0065] The electrode materials prepared in Examples 1, 2, and 3 were subjected to rate cycling tests to measure the coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) of the battery. Figure 7 and Figure 8 As shown, the electrode material loaded with nano-bismuth particles can still maintain a high efficiency at a higher current density. Among them, the CE is greater than 95% on average, and when the EE reaches 80%, the current density can be increased to 250mA / cm2, showing excellent rate performance.
[0066] (2) Long-term cycle stability Fig. 9 and Fig.10 )
[0067] At a current density of 200 mA / cm2, the battery was subjected to 200 cycles of charge and discharge testing. Fig. 9 As shown in the figure, the CE and EE of the battery remain stable during the entire cycle, and the EE is maintained between 76% and 80%. Fig.10 The change in charge and discharge capacity is shown, with a high capacity retention rate and a capacity decay rate of only 0.3% per cycle, demonstrating the excellent cycle stability and durability of the electrode material.
[0068] Result analysis: Through the above tests and characterizations, the following conclusions can be drawn: The introduction of nano-bismuth particles significantly improves the electrochemical catalytic activity of the electrode. This is attributed to the high specific surface area and abundant active sites of the nanoparticles, which accelerates the Cr3 + / Cr3 + The redox reaction kinetics of the electrode couple. The electrode material exhibits excellent rate performance and cycle stability. At high current density, the battery can still maintain a high energy efficiency, meeting the needs of practical applications for fast charging and discharging. The electrode material prepared by the plasma reduction method has the advantages of simple process and low cost. This method avoids high temperature and complex process flow, and is easy to achieve large-scale production.
[0069] Example 2
[0070] On the basis of Example 1, the plasma reduction treatment time was changed to 20 minutes, and the other steps and conditions remained unchanged.
[0071] Performance testing and result analysis
[0072] like Figure 7 As shown in the figure, as the reduction time increases, the voltage efficiency of the battery decreases slightly (within about 2%), but the overall performance is still excellent. This may be due to the fact that too long a reduction time causes the agglomeration of some nano-bismuth particles and reduces the active sites. Therefore, proper control of the reduction time is crucial to obtain the best electrode performance.
[0073] Example 3
[0074] Based on Example 1, the amount of BiCl3 was reduced by half, that is, 0.063 g BiCl 3, The concentration of bismuth ions was reduced, and the rest of the steps and conditions remained unchanged.
[0075] Performance testing and result analysis
[0076] like Figure 7 As shown in the figure, after reducing the bismuth ion concentration, the voltage efficiency of the battery decreased slightly (within about 3%), but still maintained a high performance level. This shows that although the bismuth loading has a certain effect on the electrode performance, the electrode material can still meet the requirements of efficient energy conversion within a wide concentration range.
[0077] In summary, the present invention provides a graphite felt electrode loaded with nano-bismuth particles and a preparation method thereof. By plasma reduction technology, bismuth ions adsorbed on the surface of graphite felt fibers are directly reduced to nano-scale bismuth metal particles. During the plasma reduction process, high-energy active particles (such as electrons, ions, free radicals, etc.) react rapidly and effectively with bismuth ions adsorbed on the surface of graphite felt fibers. Due to the high-density, high-energy and low-temperature characteristics of plasma, bismuth ions can be reduced to metallic bismuth atoms in a very short time. These atoms rapidly nucleate on the surface of graphite felt, and are limited by surface diffusion and growth mechanisms to form nano-scale bismuth particles with a particle size of 5 to 10 nanometers. The formation process of nanoparticles is controlled by the kinetic process of plasma reduction, which avoids excessive growth and agglomeration of particles. Compared with micron-scale bismuth particles prepared by traditional high-temperature reduction methods, nano-scale bismuth particles have a larger specific surface area and higher surface activity, can provide more active sites for electrochemical reactions, and significantly improve the electrode's Cr3 + / Cr3 + In addition, the uniform distribution of nanoparticles ensures the uniformity of catalytic activity on the electrode surface, which is beneficial to improving the overall performance of the battery.
[0078] Plasma reduction technology can be implemented at room temperature or low temperature, and has low requirements for equipment and environmental conditions. Compared with the high-temperature reduction method that needs to be carried out at temperatures of hundreds of degrees or even higher, the plasma reduction process avoids the challenges of high-temperature environments to equipment materials and energy consumption, and significantly reduces energy consumption. In addition, the plasma reduction process has a fast reaction rate, and it usually takes only 10 to 20 minutes to complete the reduction, which greatly improves production efficiency. The entire process is easy to operate. It only needs to adjust the parameters of the plasma cleaning machine (such as gas flow, RF power, vacuum degree and processing time) for precise control. The reduction conditions are easy to optimize and repeat, and the process is highly controllable.
[0079] Compared with the traditional in-situ electrodeposition method, which requires the direct addition of bismuth ions into the electrolyte, bismuth ions are electrochemically reduced on the electrode surface to form metallic bismuth. However, due to the influence of electrolyte fluidity, bismuth ions are easily over-deposited at the electrode entrance to form larger particles, which block the pore structure of the electrode, affect the flow and mass transfer process of the electrolyte, and lead to a decrease in battery performance. In contrast, the plasma reduction method first adsorbs bismuth ions on the surface of graphite felt fibers, and then reduces them to nanoscale bismuth particles in a plasma environment. Since the reduction reaction takes place on the solid surface, the problems of particle agglomeration and pore blockage caused by direct deposition in the electrolyte are avoided. The uniform distribution and appropriate size of nanoscale bismuth particles ensure that the pore structure and permeability of the graphite felt electrode are not affected, and maintain good electrolyte fluidity and electrode reaction activity.
[0080] Furthermore, the plasma reduction process is simple, and the steps involved mainly include pretreatment, impregnation, drying, plasma reduction, cleaning and drying, etc. It has few operating steps, mild process conditions, and does not require complex equipment and a high-energy consumption environment. The plasma equipment is small in size, highly operable, and easy to integrate into existing production lines. In addition, the plasma reduction process is easy to automate and continuously produce, and the production scale can be adjusted by controlling the equipment parameters to meet the needs of industrial production. Compared with the high-temperature reduction method, the plasma reduction method reduces production costs.
[0081] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a graphite felt electrode loaded with nano-bismuth particles, characterized in that: The method comprises the following steps: Pre-treating the graphite felt electrode to obtain a hydrophilic graphite felt electrode; Immersing the hydrophilic graphite felt electrode in a solution containing bismuth ions, taking it out and drying it to obtain a graphite felt loaded with reduced bismuth precursor crystals; The graphite felt loaded with reduced bismuth precursor crystals is treated with plasma to obtain a graphite felt electrode loaded with nano-bismuth particles.
2. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 1, characterized in that: The pretreatment is heating pretreatment, wherein the heating temperature is 400-500° C. and the insulation time is 4-5 hours.
3. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 1, characterized in that: The concentration of bismuth ions in the solution is 0.01-0.04 mol / L.
4. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 1, characterized in that: The drying condition is baking at 80-100° C. for 2-3 hours.
5. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 1, characterized in that: The graphite felt loaded with reduced bismuth precursor crystals is treated with plasma, comprising: placing the graphite felt loaded with reduced bismuth precursor crystals in a plasma cleaning device, adjusting the parameters of the plasma cleaning device to reduce bismuth ions, and obtaining a graphite felt electrode material loaded with bismuth metal particles and bismuth oxychloride particles; The graphite felt electrode material loaded with bismuth metal particles and bismuth oxychloride particles is cleaned and dried to obtain the graphite felt electrode loaded with nano-bismuth particles.
6. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 5, characterized in that: The parameters include: air flow rate of 40-60 ml / min, radio frequency power of 100-150 W, vacuum degree of 10-20 Pa, and cleaning time of 10-20 min.
7. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 1, characterized in that: The particle size of the nano-bismuth particles is 5-10 nm.
8. The method for preparing a graphite felt electrode loaded with nano-bismuth particles according to claim 1, characterized in that: The solution is a hydrochloric acid solution containing bismuth ions, and the concentration of the hydrochloric acid solution is 1-3 mol / L.
9. A graphite felt electrode loaded with nano-bismuth particles, characterized in that: The graphite felt electrode loaded with nano-bismuth particles is prepared by the preparation method described in any one of claims 1 to 8.
10. An iron-chromium or all-vanadium liquid flow battery, characterized in that: The iron-chromium or all-vanadium liquid flow battery comprises the graphite felt electrode loaded with nano-bismuth particles as claimed in claim 9.
Citation Information
Patent Citations
Primary alkaline battery containing bismuth metal oxide
CN101167212A
Preparation method for hydrogen energy-powered low-temperature fuel cell electrode catalyst
CN102744110A
Quick and effective modification method of graphite felt for vanadium battery
CN108054390A
Method for preparing graphite felt electrode material loaded with bimetallic particles through reduction method
CN118099459A
Modification method of bismuth-doped graphite felt
CN118676391A
Cited By
Graphite / bismuth nanosheet electrocatalytic anode material as well as preparation method and application thereof
CN120714611A
Bismuth metal modified electrode, preparation method, application and all-vanadium redox flow battery
CN121054714A
A bismuth metal modified electrode, a preparation method, application and a full vanadium redox flow battery
CN121054714B